1994
DOI: 10.1172/jci117578
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of experimental autoimmune encephalomyelitis with a hydroxamate inhibitor of matrix metalloproteases.

Abstract: Gelatinases, belonging to the matrix metalloproteases, con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
201
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(210 citation statements)
references
References 20 publications
8
201
0
1
Order By: Relevance
“…Elevated levels of MMP-9 are found around the time of onset of symptoms and the MMP inhibitor, GM6001, blocked the BBB injury and improved the clinical condition (Gijbels et al, 1994). Other studies, using different synthetic MMP inhibitors, have shown similar results (Hewson et al, 1995;Liedtke et al, 1998).…”
Section: Mmps In Neuroinflammation In the Absence Of Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of MMP-9 are found around the time of onset of symptoms and the MMP inhibitor, GM6001, blocked the BBB injury and improved the clinical condition (Gijbels et al, 1994). Other studies, using different synthetic MMP inhibitors, have shown similar results (Hewson et al, 1995;Liedtke et al, 1998).…”
Section: Mmps In Neuroinflammation In the Absence Of Hypoxiamentioning
confidence: 99%
“…TIMP-2 blocked the MMP-2-induced BBB opening in MMPinduced injury in the brain (Rosenberg et al, 1992). Damage to the BBB was blocked, and symptomatic improvement occurred in experimental allergic encephalomyelitis (EAE) with hydroxymate treatment (Gijbels et al, 1994;Hewson et al, 1995;Clements et al, 1997). BB-94 blocked the BBB opening after intracerebral injection of TNF-␣, and BB-1101 was effective in LPS-induced BBB injury MunBryce and Rosenberg,1998a).…”
Section: Synthetic Mmp Inhibitorsmentioning
confidence: 99%
“…Interestingly, the expression of various MMPs is increased in MS [10,31] and EAE [8]. Inhibitors of MMP also block the development of EAE [4,17,22]. The effects of PPAR-γ agonists on MMP expression in the CNS have not been thoroughly investigated.…”
Section: Ppar-γ: Effects On Peripheral Leukocytesmentioning
confidence: 99%
“…Severe EAE in MMP-2 null mice is believed to be due to the elevated MMP-9 levels seen in these animals (Esparza et al, 2004). Conversely, young MMP-9 null mutant mice are resistant to EAE (Dubois et al, 1999) and it is possible to partially suppress EAE using MMP inhibitors (Gijbels et al, 1994;Hewson et al, 1995;Nygardas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%